2022
DOI: 10.1111/jocn.16303
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal buprenorphine improves overall quality of life and symptom severity in cancer patients with pain

Abstract: Aim and Objectives This study explored the effect of transdermal buprenorphine on quality of life and six symptoms in cancer patients with pain. Background Transdermal opioids offer advantages over traditional routes of administration. The impact of transdermal buprenorphine on quality of life for patients with cancer in Asian populations is unknown. Design This study employed a single‐arm observational repeated measures design. Cancer patients with pain were evaluated prior to treatment (baseline). Over a 4‐w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Opioids are frequently used to manage cancer pain [15][16][17][18][19][20][21], due to their effectiveness and inclusion in clinical guidelines/recommendations [4][5][6][7][8]. Furthermore, studies have shown that opioids can improve QOL by alleviating cancer-related pain [22][23][24][25][26][27]. Here, we have shown that two formulations of tramadol can achieve a clinically relevant improvement in cancer pain at rest and during movement, and both formulations were comparable in terms of other outcomes, including sleep quality, use of rescue medications, and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids are frequently used to manage cancer pain [15][16][17][18][19][20][21], due to their effectiveness and inclusion in clinical guidelines/recommendations [4][5][6][7][8]. Furthermore, studies have shown that opioids can improve QOL by alleviating cancer-related pain [22][23][24][25][26][27]. Here, we have shown that two formulations of tramadol can achieve a clinically relevant improvement in cancer pain at rest and during movement, and both formulations were comparable in terms of other outcomes, including sleep quality, use of rescue medications, and QOL.…”
Section: Discussionmentioning
confidence: 99%